THE METAPHOR OF "MAGIC BLACKBOARD" TO RETHINK AN EXPERIENCE IN TEACHING OF VISUAL ARTS - Angélica D’Avila Tasquetto; Marilda Oliveira de Oliveira (Travessias, 2009)
The present study has its bases in an experience with the Teaching of Visual Arts accomplished in a school level with students of the medium teaching from the Cilon Rosa School, in Santa Maria RS. In order to establish some reflections about this experience we have started from the optics which is based on the metaphor of Magic Blackboard, where we have the purpose of making considerations regarding the livid experience as Art/Educating. Furthermore, this work aims at presenting some considerations regarding the docent paths with the intent to highlight life experiences as mediators for the building of the knowledge of the area of Teaching of Visual Arts. Taking in to account that we can offer to the students the access to the contemporaneous artistic means, the memory, the path and the docent experience are emphasized as a way that make possible changes and transformations in the education, mainly in the area of Teaching of Visual Arts. To understand the process of actuation of the professional in Teaching of Art means to recognize its path and experiences in order to reach an understanding on docent memory and the aspects that bring dynamism to their representations as educators. Thus, the subjects on docent memories and paths are important while they allow analyzing the complexities of the educative subjects and proposing an education that pay attention to the differences, including the ones of space